Effect of novel atmospheric‐pressure jet pretreatment on the drying kinetics and quality of white grapes. (30th May 2019) - Huang, Chien‐Chih; Wu, James Swi‐Bea; Wu, Jong‐Shinn; Ting, Yuwen
Abstract: BACKGROUND: Raisin is a popular snack and a common constituent of many foods owing to its good flavor and nutritional value. Conventional drying of grapes can be a slow and energy‐consuming process as their waxy surface hinders efficient moisture migration. A drying pretreatment that disrupts the waxy cuticle is usually applied to increase the drying rate. RESULTS: The application of an atmospheric‐pressure air plasma jet to the grape surface could effectively enhance the drying kinetics and decrease the drying time by more than 20%. Through etching of the waxy cuticle, the air plasma jet optimally improves the quality of the final product. Although the surface hydrophilicity was increased by 40%, the physical appearance, color, and texture of plasma‐treated raisins were similar to the product from untreated control and chemical‐treated groups. A more than twofold increase in the total phenolic content and antioxidant capacity was observed when compared to other experimental groups. CONCLUSIONS: The results indicate that atmospheric plasma could be a better option than using chemicals to pretreat grapes before drying since it leaves no toxic residue, while successfully preserving the product quality. This work shows the great potential for the application of atmospheric air plasma in the drying of food materials. © 2019 Society of Chemical Industry